Maternal and fetal leptin, adiponectin levels and associations with fetal insulin sensitivity1. (16th March 2013) - Luo, Zhong‐Cheng; Nuyt, Anne‐Monique; Delvin, Edgard; Fraser, William D.; Julien, Pierre; Audibert, Francois; Girard, Isabelle; Shatenstein, Bryna; Deal, Cheri; Grenier, Emilie; Garofalo, Carole; Levy, Emile
Abstract Objective: It remains uncertain whether leptin and adiponectin levels are correlated in maternal vs. fetal circulations. Little is known about whether leptin and adiponectin affect insulin sensitivity during fetal life. Design and Methods: In a prospective singleton pregnancy cohort (n = 248), we investigated leptin and adiponectin concentrations in maternal (at 24‐28 and 32‐35 weeks of gestation) and fetal circulations, and their associations with fetal insulin sensitivity (glucose/insulin ratio, proinsulin level). Results: Comparing concentrations in cord vs. maternal blood, leptin levels were 50% lower, but adiponectin levels more than doubled. Adjusting for gestational age at blood sampling, consistent and similar positive correlations (correlation coefficients: 0.31‐0.34, all P < 0.0001) were observed in leptin or adiponectin levels in maternal (at 24‐28 or 32‐25 weeks of gestation) vs. fetal circulations. For each SD increase in maternal plasma concentration at 24‐28 weeks, cord plasma concentration increased by 12.7 (95% confidence interval 6.8‐18.5) ng/ml for leptin, and 2.9 (1.8‐4.0) µg/ml for adiponectin, respectively (adjusted P < 0.0001). Fetal insulin sensitivity was negatively associated with cord blood leptin (each SD increase was associated with a 5.4 (2.1‐8.7) mg/dl/µU/ml reduction in cord plasma glucose/insulin ratio, and a 5.6 (3.9, 7.4) pmol/l increase in proinsulin level, all adjusted P < 0.01) but not adiponectin (P > 0.4) levels). Similar associations were observed in nondiabetic full‐term pregnancies (n = 211). Conclusions: The results consistently suggest a maternal impact on fetal leptin and adiponectin levels, which may be an early life pathway in maternal‐fetal transmission of the propensity to obesity and insulin resistance.